An efficient three-dimensional multiphase fluid structure interaction model on GPU for water impact of a moving body with complex geometries. (15th December 2022) - Xin, Jianjian; Shi, Fulong; Chen, Zhenlei; Xu, Guochun
Abstract: This paper presents an efficient three-dimensional (3D) multiphase fluid structure interaction (FSI) model to simulate water impact of complex moving bodies in ocean engineering. This numerical model adopts an improved ghost cell method (GCM) to enforce the boundary conditions on the moving boundaries and the gradient augmented level set (GALS) method to capture the nonlinear free surfaces. An improved iso-surface representation method is highlighted to track arbitrary moving bodies such as sharp or concave shapes. Also, a GPU-CUDA parallel framework is incorporated to greatly accelerate the computational performance. The accuracy and capability of the present model is validated by simulating 3D water entry of arbitrary free-falling bodies (a sphere, a wedge, a wedge with side plates, and a catamaran). Excellent acceleration performance of the present GPU model is demonstrated. The present results including the slamming coefficient, the acceleration, and the local pressure agree satisfactorily with the experimental data. The complex flow evolutions are well captured such as long cavity wall, the pinch-off of the cavity, and the air entrapment. Also, the air entrapment and 3D effects are confirmed to be nonnegligible for the water impact of complex bodies with enclosed sections, which can be well predicted by the present model. Highlights: A 3D multiphase fluid structure interaction model on GPU is presented. An iso-surface representation method is highlighted to track 3D complex geometries. The present GPU based model can achieve excellent acceleration performance. The present model can well predict the water impact of 3D complex geometries. The air entrapment and 3D effects were analyzed for complex bodies.